PENGARUH TOTAL SERVISE QUALITY MANAGEMENT TERHADAP KEPUASAN PELANGGAN - Suryo, Prastowo; Fajarwati, Fajarwati (Jurnal Analisis Bisnis Ekonomi, 2010)
This research was conducted to analyze the influence of Total Service Quality Management (TSQM) to the customers satisfaction (the customers meant in this research were the business class train passengers of Tugu Railway Station Yogyakarta) by using 5 dimensions of TSQM (Said, 2004) i.e: physical quality dimension, supporting physical quality, company/institution quality, technical quality dimension, and interactive quality dimension. The method used for data collecting was survey method by giving quetionaires to the respondents. The technique used to take the samples of the research was purposive sampling. Out of 100 samples collected, only 94 samples were eligible to be prossed further. In this research validity and reliability tests were conducted to ensure the validity and reliability of the research instruments. Data analysed used in the research were multiple linear regression, t test, and F test. The result of the research shows that there is an influence of TSQM to the customers satisfaction on the dimentions of physical quality dimension, supporting physical quality, company/institution quality, technical quality dimension, and interactive quality dimension forward the business class train passengers, both partially and simultaneously of all dimension. The most influential dimensions to the customers satisfaction is the physical quality dimension.